STRATEGI PENGEMBANGAN LEMBAGA KEUANGAN MIKRO AGRIBISNIS PERDESAAN DI KECAMATAN SEWON - Diyas Harjanti (EKPI 16 UMY 074, 2016)
*74 In the agricultural sector, such as in the rural areas, agribusiness is dominated by micro enterprises a business selling fertilizer, seeds and inputs, products processing, and traders of agricultural products. The fundamental problem faced by entrepreneurs in agribusiness. Is shortage of capital sources, technology and market access. To overcome these problems the government provide financial assistance of Rural Agribusiness Development through Gapoktan and managed by LKM-A. This study aims to determine the performance of LKM-A in fund management, to determine the role of LKM-A for the welfare of members and to formulate development strategies of LKM-A in Sewon District. Analytical method used in this research is quantitative descriptive analysis and SWOT analysis. The populations are two LKM-A in the Sewon District, namely MFI-A Gemah Ripah and Tani Makmur. For sampling in this study using purposive sampling method and sample size was 73 respondents.The results show that the performance of LKM-A Gemah Ripah and Tani Makmur are good. This is because of both of LKM-A are well managed, such as lacking facilities and limited infrastructure and for the sanctions to borrowers who jammed still low. For the role of LKM-A Gemah Ripah and Tani Makmur for the welfare of the members are already well organized and the response of members of the financing provided is able to increase the yield of the business. And the need to done economic conditions are getting better and strategies for the development of LKM-A by increasing capital sources owned by LKM-A, improve supervision and assistance to management and members, improve the quality of services and human resources management and members as well as open up marketing network generated by the sale of LKM-A members. Keywords: Strategy, SWOT, LKM-A, Capital